Effect of TiO2 nanofluid and hybrid TiO2 nanofluid on mechanical properties of steels for automotive applications - Radhiyah, Abd Aziz (IOP Publishing, 2020)
Quenching is a process involving rapid cooling in quenching media and hardening of steels. The effect of quenching process on the microstructure and mechanical properties (hardness) are studied and elaborated in this thesis. The quenching media uses including conventional fluid (distilled water and mineral oil), nanofluid (TiO2 nanofluid), and hybridbased nanofluid (TiO2 hybrid nanofluid). Thermal conductivity and microstructure development are closely-linked to each other. Conventional fluids as quenching media have low thermal conductivity thus limiting the development of desired microstructure in the steels. The thermal conductivity and stability of nanofluid and hybrid-based nanofluid are studied to enhance the thermal properties of the quenching media.